Republic of Moldova : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
In this paper, the following statistical data were listed in detail: GDP by both expenditure and sector, industrial production by sector, agricultural and industrial production indices, structure of agricultural land ownership, agricultural production by sector, nominal wages by sector, monthly prices, exchange rates, employment by sector, exchange rates, central and local government operations, central and local government expenditure, monetary survey, balance of payments, composition and direction of trade, accounts of the national bank of Moldova, import tariff developments, and external debt indicators.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet